Therapy of Mental Disorders in Adolescents: An Analytical Study of Tafsir Al-Misbah - Bahari, Lalu Pradipta Jaya; Burhanudin, Burhanudin; Hamzanwadi, Hamzanwadi (Program Studi Bimbingan dan Konseling Islam (BKI) Fakultas Ushuluddin, Adab dan Dakwah (FUAD) Institut Agama Islam Negeri (IAIN), 2024)
The discussion about adolescents is a broad discussion when it comes to the current era, especially when discussing their colorful lives, both drama and conflict. However, there are things that are the subject of discussion that need to be studied scientifically, namely related to behavior, mentality and psychology in adolescents. especially now that we find many teenagers, especially in Indonesia, have mental disorders, ranging from low intensity to those that can cause negative behavior and even worse can have an impact on suicide. The urgency in understanding adolescents is very necessary considering that adolescents are the hope of the community who will be the successor in the future. This research aims to analyze and provide solutions related to mental disorders in adolescents by using the Qur'anic perspective and reviewed based on contemporary interpretations and psychotherapy. This research uses psychoanalysis and phenomenon study methods using a descriptive qualitative approach. This research is expected to be a reference for parents, communities and other people in understanding how dangerous mental disorders in adolescents are.